Rethinking the Employees’ Perceptions of Corporate Citizenship Dimensionalization - Rego, Arménio ca. 20.-21. Jh.; Leal, Susana; Cunha, Miguel Pina e 1965- (2011)
The article suggests that the four-factor model of corporate citizenship (CC: economic, legal, ethical, and discretionary responsibilities) does not fairly represent all pertinent dimensions of employees’ CC perceptions. Based on an empirical study with a sample of 316 employees, we show that, at least in some contexts, individuals distinguish seven CC dimensions: (1) economic responsibilities toward customers; (2) economic responsibilities toward owners; (3) legal responsibilities; (4) ethical responsibilities; (5) discretionary responsibilities toward employees; (6) discretionary responsibilities toward the community; and (7) discretionary responsibilities toward the natural environment. We do not suggest that this seven-factor model represents all of the (more) relevant CC dimensions in the employees’ minds. We aim to share evidence showing that the four-factor model proposed by Maignan et al. (Journal of the Academy of Marketing Science 27(4):455–469, 1999) may be refined, at least when the employees are the stakeholders in question.
Keywords: Discretionary responsibilities toward natural environment; Discretionary responsibilities toward community; Discretionary responsibilities toward employees; Economic responsibilities toward owners; Economic responsibilities toward customers; Corporate Citizenship